Determinación de fructosamina, hemoglobina glicosilada y glucosa basal para el control de terapia en el Club de Diabéticos del Hospital General Isidro Ayora de la ciudad de Loja - Marín Alvarado, Ana Gabriela (2015)
Diabetes mellitus type 2 (DM2 ) is a common chronic disease of high prevalence, which is characterized by a high level of blood glucose, with a high social cost and a large health impact, developing acute and chronic complications, accelerates damage to major organs, which increased morbidity and mortality especially in the elderly population due to changes in lifestyle and eating habits. For this reason it was developed to complement the diagnostic tests and to estimate their glycemic condition during different time periods. Therefore this research, descriptive and cross-sectional in patients who attended the Diabetic Club General Hospital Isidro Ayora Loja City was held, whose objective was to determine the levels of fructosamine, glycated hemoglobin (HbA1c) and fasting glucose in fasting, as parameters of metabolic control and direct relationship between these values, processing 65 samples from patients diagnosed with type 2 Diabetes Mellitus, the determination of these tests are performed using the photometric method. The results evidenced that 50.77% had fasting glucose levels increased, while 60% had glycated hemoglobin levels above 6.5% that is altered values, and 41.54% showed high levels of fructosamine, so by relating the 3 parameters provides that if there is a correlation with each other, being the most altered HbA1c test showing poor glycemic control for 3 months. Concluding that the majority of this population presented hyperglycemia ie poor metabolic control and have greater risk of triggering chronic complications, and that the 3 tests used serve to control its glycemic state. Key words: Diabetes Mellitus type 2, fructosamine, HbA1c, glucose.